A novel cleanliness control method for disk amplifiers. (28th December 2020) - Li, Yangshuai; Wang, Bingyan; Zhang, Panzheng; Zhang, Yanli; Zhang, Yanfeng; Zhou, Shenlei; Ma, Weixin; Zhu, Jianqiang
Abstract: As the key part for energy amplification of high-power laser systems, disk amplifiers must work in an extremely clean environment. Different from the traditional cleanliness control scheme of active intake and passive exhaust (AIPE), a new method of active exhaust and passive intake (AEPI) is proposed in this paper. Combined with computational fluid dynamics (CFD) technology, through the optimization design of the sizes, shapes, and locations of different outlets and inlets, the turbulence that is unfavorable to cleanliness control is effectively avoided in the disk amplifier cavity during the process of AEPI. Finally, the cleanliness control of the cavity of the disk amplifier can be realized just by once exhaust. Meanwhile, the micro negative pressure environment in the amplifier cavity produced during the exhaust process reduces the requirement for sealing. This method is simple, time saving, gas saving, efficient, and safe. It is also suitable for the cleanliness control of similar amplifiers.